Tools for Identifying Potentially Inappropriate Prescriptions for Children and Their Applicability in Clinical Practices: A Systematic Review - Li, Siyu; Huang, Liang; Chen, Zhe; Zeng, Linan; Li, Hailong; Diao, Sha; Jia, Zhi-Jun; Cheng, Guo; Yu, Qin; Zhang, Lingli (Frontiers in Pharmacology, 2022)
Background: The safety of drug use for children is a global public health problem. The potentially inappropriate prescribing (PIP) screening tools are expected to reduce ADR and promote rational drug use. Objectives: To systematically evaluate children’s potentially inappropriate prescription screening tools and empirical studies on these tools, to promote the development of this field and provide directions for subsequent research. Methods: We systematically searched 6 databases including PubMed, Embase, Cochrane Library, CNKI, VIP, Wanfang. Two reviewers independently selected articles by the inclusion and exclusion criteria and extracted data. Then we evaluated the coverage of diseases or drugs in these tools and calculated the number of items and the coincidence rate of items among tools. Results: 5 children’s PIP screening tools were identified, most children's PIP screening tools were developed by using Delphi expert consensus and focused on respiratory system drugs, anti-infective drugs, and gastrointestinal drugs. The coincidence rates of the POPI and the POPI Int, the POPI and the POPI UK were 69.52% and 38.06% respectively; the coincidence rates of the POPI UK and the POPI int, the POPI UK and the PIPc were 36.61% and 1.10% respectively; The KIDs List did not overlap other 4 tools. Only the POPI tool developed by French experts had study results showing its feasibility and reliability in French clinical practice. In general, the coincidence rates of children's PIP screening tools were not high and lacking empirical studies on children’s PIP screening tools. Conclusion: The study on the screening tools of inappropriate prescriptions for children is a neglected research field. More researchers need to develop their countries' PIP screening tools for children based on the best available clinical evidence and the actual situation of their countries.